Moluscos continentales de México: Terrestres - Naranjo García, Edna (Revista de Biología Tropical, 2003)
Mexico has 41 land mollusc families: 7 Prosobranchia and 34 Pulmonata. For each species, a brief account of ecology is presented (habitat, vegetation, humidity level, soil type and elevation). These molluscs are widely distributed in a variety of habitats, but no prosobranchs have been reported from two states: Sonora and Baja California. Reproduction, behavior coloration, aestivation and hibernation have been reported for some species. Food and humidity are key factors. Life span is associated with body size; in addition some semi-slugs live a year. Biogeography studies have been patchy and only cover the provinces: Altiplano, Sierra Madre Oriental, Veracruzana, Southwest USA (enters México by Sonora), Mexican Midwest, and in Baja California: California, Sonora and Cabo.